The Characteristic-Based Split (CBS) scheme-a unified approach to fluid dynamics - Nithiarasu, P.; Codina, R.; Zienkiewicz, O. C. (International journal for numerical methods in engineering, 2006)
This paper presents a comprehensive overview of the characteristic‐based methods and Characteristic‐Based Split (CBS) scheme. The practical difficulties of employing the original characteristic schemes are discussed. The important features of the CBS scheme are brought out by studying several problems of compressible and incompressible flows. All special consideration necessary for solving these problems are thoroughly discussed. The CBS scheme is presented in such a way that any interested researcher should be able to develop a code using the information provided. Several invicid and viscous flow examples are also provided to demonstrate the unified CBS approach. For sample two‐dimensional codes, input files and instructions, the readers are referred to ‘www.nithiarasu.co.uk’ Copyright © 2006 John Wiley & Sons, Ltd.